Drivers and barriers for open innovation for sustainability in a shared semiconductor infrastructure - Piia Konstari; Katri Valkokari (Journal of Open Innovation: Technology, Market and Complexity)
A shared-use semiconductor research infrastructure can be studied as a local innovation ecosystem consisting of the infrastructure operating company and the user companies. The level of open innovation for sustainability activities possible to initiate in the infrastructure is affected by the operating company and the user companies. This study focuses on developing a conceptual framework for analysing the drivers and barriers for open innovation for sustainability in the research infrastructure. The research is done as a qualitative multiple case-study in the local semiconductor ecosystem in Otaniemi, Finland. We find out that the level of understanding and ambitions related to sustainability are diverse in the different user companies. Many factors can be considered both as drivers and barriers for open innovation for sustainability depending on the context and the companies’ ambition levels. The sustainability of a shared-use infrastructure is a complex topic that requires further research to better understand how open innovation for sustainability related activities can be brought forward in such an ecosystem. The study contributes to the current understanding of open innovation for sustainability by recognising the role of shared-used research infrastructure in innovation processes within the local ecosystem.